Training to Teach in Primary Schools A practical guide to School-based training and placements. - Medwell, Jane A. (SAGE Publications, 2015)
With guidance on adapting to work in school, teaching on placement, securing the first teaching job, and succeeding in the NQT year, this book is a must-have for primary trainees on school experience, whether they are in a school-based or university-based teacher training programme.